The Paradigm of Innovative Economic Development: a New Philosophy or the Basis of Evolu-tion in the Conditions of Digitalisation - Kamchatova, Ekaterina; Burlakov, Vyacheslav; Dzyurdzya, Olesya; Yeremyan, Ara (Տիգրան Մեծ)
This article discusses the processes of implementing innovative prospects for developing the Russian economy in thecontext of digitalisation. Currently, in countries with a high level of innovation component in all spheres of economic activity, innovation is fundamental for the development of the economies of these countries. Innovative development is an integral partof economic development philosophy in countries such as Germany, Sweden, Japan, South Korea, China, the USA, and other developed countries. Un-like the countries mentioned above, the economy of the Russian Federation, despite the existing high innovation potential, is an economy in need of significant refinement. Innovations must be the basis of modern philosophy and the development and transformation of the Russian economy. The authors consider the model of innovative development and the processes associated with the improvement of innovation as a philosophy of development and transformation, which will provide the basis for the economy‟s evolution in the current situation and increase the competitiveness of enterprises of the Russian Federation. In the article, the latency of innovation is proposed as an aspect of innovative development –to transform existing developments and generate new ideas.
Keywords: Philosophy of economics